2007
DOI: 10.2174/138161207781368729
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation and Pharmacology of Pacemaker Channels

Abstract: The spontaneous activity of cardiac tissue originates in specialized pacemaker cells in the sino-atrial node that generate autonomous rhythmic electrical impulses. A number of regions in the brain are also able to generate spontaneous rhythmic activity to control and regulate important physiological functions. The generation of pacemaker potentials relies on a complex interplay between different types of currents carried by cation channels. Among these currents, the hyperpolarization-activated current (termed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…In good agreement with the findings of earlier studies [16,33,34], the present observations disclosed that the presence of CIL was able to suppress the amplitude of hyperpolarization-elicited I h , as well as to slow the rate of the current activation (Figure 1). There was a distinct hyperpolarizing shift in the midpoint of the activation curve of I h in its presence with no alterations in the gating charge of the current (Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…In good agreement with the findings of earlier studies [16,33,34], the present observations disclosed that the presence of CIL was able to suppress the amplitude of hyperpolarization-elicited I h , as well as to slow the rate of the current activation (Figure 1). There was a distinct hyperpolarizing shift in the midpoint of the activation curve of I h in its presence with no alterations in the gating charge of the current (Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…[193]) is controversial. New evidence in favor to a direct binding of genistein to the channel comes from a recent paper by Rozario et al [194], where the effect of genistein was measured on wt mHCN1 and mHCN2 and on mutants where a critical arginine in the CNBD has been replaced with glutamate (mHCN1-R538E and mHCN2-R591E).…”
Section: Substances That Have Been Shown To Modulate Hcn Channel Actimentioning
confidence: 99%
“…The pacemaker activity of sinoatrial node (SAN) cells in the mammalian heart arises from the integrated action of multiple sarcolemmal ionic channel currents and the interaction between the intracellular calcium handling and sarcolemmal electrogenic processes (Irisawa et al, 1993;Mangoni and Nargeot, 2008;Lakatta et al, 2010). The hyperpolarization-activated "funny" current, I f , present in the SAN and other regions of the cardiac conduction system (Boyett, 2009;Difrancesco, 2010), is produced by the hyperpolarization-activated cyclic nucleotide gated (HCN) channel isoforms (of which there are four: HCN1-4), each of which is comprised of six transmembrane domains with four subunits combining to produce functional tetrameric channels, as occurs for voltage-gated potassium channels (Bois et al, 2007;Difrancesco, 2010). Previous studies of the rabbit SAN have shown that although HCN isoforms 1, 2, and 4 are all expressed in the heart, HCN4 is the most abundant in the SAN and the I f density within SAN sub-regions correlates strongly with HCN4 expression levels (Thollon et al, 2007;Brioschi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%